Prevalence and Risk Factors for HTLV-1/2 Infection in Quilombo Remnant Communities Living in the Brazilian Amazon - Brito, Wandrey Roberto dos Santos; Cardoso-Costa, Greice de Lemos; Roland Junior, Lourival Marques; Pereira, Keise Adrielle Santos; Lopes, Felipe Teixeira; Santos, Bernardo Cintra dos; de Lima, Aline Cecy Rocha; Abreu, Isabella Nogueira; Lima, Carlos Neandro Cordeiro; Lima, Sandra Souza; Cayres Vallinoto, Izaura M. Vieira; Santos, Eduardo José Melo dos; et al. (Frontiers in Public Health, 2022)
Human T-lymphotropic viruses 1 and 2 (HTLV-1 and HTLV-2) are retroviruses that originated on the African continent and dispersed throughout other continents through human migratory flows. This study describes the prevalence of HTLV-1 and HTLV-2 infection in residents of 11 quilombo remnant communities in the state of Pará, Brazil, and the associated risk factors. A total of 859 individuals (334 men and 525 women), aged between 7 and 91 years, participated in the study. All subjects answered a questionnaire with questions on sociodemographic characteristics and on risk factors associated with HTLV infection, and blood samples were collected and separated into plasma and leukocytes. An immunoenzymatic assay (ELISA; Murex HTLV-I+II, DiaSorin, Dartford, UK) was used as a screening test, and positive samples were subjected to line immunoassay confirmatory tests (Inno-LIA HTLV I/II Score FUJIREBIO) and DNA extraction for subsequent real-time PCR to differentiate the viral type. Four of the 859 individuals were seropositive for HTLV. HTLV-1 infection was confirmed in one individual from the Itamoari community (0.92%), and HTLV-2 infection was confirmed in two individuals from São Benedito (3.17%) and in one individual from Arimandeua (2.22%). Blood transfusion was the only risk factor associated with HTLV infection in this study. This study reports the occurrence of HTLV-1 and HTLV-2 in quilombo remnant communities in the state of Pará. Considering the African origin of the virus and its introduction into Brazil from the slave trade, the continued evaluation of quilombola communities in the state of Pará is essential to better characterize the distribution of infections in these populations and to create public health policies for the control of the spread of the virus and associated diseases.